Crime and punishment in the Jim Crow South - Wood, Amy Louise; Ring, Natalie J. (University of Illinois Press, 2019)
The trials of George Doyle: race and policing in Jim Crow New Orleans / K. Stephen Prince -- "Many people 'colored' have come to the homicide office": police investigations of African American homicides in Memphis, 1920-1945 / Brandon T. Jett -- Forced confessions: police torture and the African American struggle for civil rights in the 1930s and 1940s South / Silvan Niedermeier -- The South's Sin City: white crime and the limits of law and order in Phenix City, Alabama / Tammy Ingram -- Testimonial incapacity and criminal defendants in the South / Pippa Holloway -- Sewing and spinning for the state: incarcerated black female garment workers in the Jim Crow South / Talitha L. LeFlouria -- Cole Blease's pardoning pen: state power and penal reform in South Carolina / Amy Louise Wood -- Hanging, the electric chair, and death penalty reform in the early twentieth-century South / Vivien Miller -- The making of the modern death penalty in Jim Crow North Carolina / Seth Kotch